Production of the novel fibrous structure of poly(epsilon-caprolactone)/tri-calcium phosphate/hexagonal boron nitride composites for bone tissue engineering - OKTAR, FAİK NÜZHET; EKREN, NAZMİ; GÜNDÜZ, OĞUZHAN (AUSTRALIAN CERAMIC SOCIETY, 2018)
Nanofibrous composites of the poly(epsilon-caprolactone) (PCL), tricalcium phosphate (TCP), and hexagonal boron nitride (h-BN) with different compositions were manufactured by using an economical and non-complicated method called electrospinning. Produced fibrous structures showed no bead formation and had a clean surface. Characterization of the composites showed that particles were successfully mixed with polymer phase. High cell activity of SaOS-2 cells on the composites was observed with SEM images. In addition, fibrous scaffolds are biocompatible with human bone tissue and are highly degradable.
Keywords: Biopolymers; Biofibers; Biomaterials; Poly(epsilon-caprolactone); Composites; POLYCAPROLACTONE; SCAFFOLDS; FABRICATION